2005
DOI: 10.1191/0269215505cr862oa
|View full text |Cite
|
Sign up to set email alerts
|

Movement skill assessment in children with profound multiple disabilities: a psychometric analysis of the Top Down Motor Milestone Test

Abstract: The reliability of the TDMMT is good, but validity is moderate. Results indicate that adaptations to the structure of the TDMMT should be made when used for children with profound multiple disabilities. Further psychometric evaluation of the TDMMT is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…outcomes research with children functioning at GMFCS levels IV and V and provided information on the tools psychometric properties and clinical utility. The tools include the 10-meter (10-m) walk test [26,27], 10-minute (10-min) walk test [27], Directional Mobility Assessment (DMA) [24,25], Gross Motor Function Measure (GMFM) [28], Pediatric Evaluation of Disability Inventory (PEDI) [29], Physical Abilities and Mobility Scale (PAMS) [30], School Function Assessment (SFA)-Travel subscale [31], Step/leg movement count [16,20,21,32], Step length and velocity footprint analysis [24,25], Top Down Motor Milestone Test (TDMMT) [33], Videoing indices of happiness [19,21], and the Functional Independence Measure for children (Wee FIM) [34,35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…outcomes research with children functioning at GMFCS levels IV and V and provided information on the tools psychometric properties and clinical utility. The tools include the 10-meter (10-m) walk test [26,27], 10-minute (10-min) walk test [27], Directional Mobility Assessment (DMA) [24,25], Gross Motor Function Measure (GMFM) [28], Pediatric Evaluation of Disability Inventory (PEDI) [29], Physical Abilities and Mobility Scale (PAMS) [30], School Function Assessment (SFA)-Travel subscale [31], Step/leg movement count [16,20,21,32], Step length and velocity footprint analysis [24,25], Top Down Motor Milestone Test (TDMMT) [33], Videoing indices of happiness [19,21], and the Functional Independence Measure for children (Wee FIM) [34,35].…”
Section: Resultsmentioning
confidence: 99%
“…In the expanded search, methodological studies providing further information on the Top Down Motor Milestone Test [33,36], use of the 10-m walk test with children with CP GMFCS levels I-III [37,38], and the PAMS [39] were identified. Only one gait trainer intervention study not included in the systematic review was identified [40].…”
Section: Tool Identificationmentioning
confidence: 99%
“…As for cognitive and developmental assessment, instruments like the Behavioural Assessment Battery (Kiernan & Jones, 1982) and the Ordinal Scales of Psychological development (Užgiris & Hunt, 1975) are still widely used, and revised versions of these instruments have led to new instruments such as the Behavioral Appraisal Scales (Vlaskamp, Van der Meulen, & Zijlstra, 2002). Several instruments regarding motor and sensory functioning are available, such as the Top Down Motor Milestone Test (van der Putten et al., 2005). Methods of assessment of adaptive behavior skills are more or less limited to communicative skills.…”
Section: Assessment Methodsmentioning
confidence: 99%
“…These measures are reported to have good test-retest reliability for children with disabilities. The only multiple baseline study 31 used the Top Down Motor Milestone Test, with modifications 40 and reports that it is a useful evaluative tool for measuring functional motor outcomes in children with severe and profound disabilities. Outcomes were divided into ICF 11,12 components with details shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%